Simple, economical, and environmentally benign protocol for the synthesis of 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Desai, Uday V.; Kulkarni, Makarand A.; Pandit, Kapil S.; Kulkarni, Aparna M.; Wadgaonkar, Prakash P. (Green Chemistry Letters and Reviews, 2014)
A simple, economical, and environmentally benign protocol has been described for one-pot synthesis of medicinally privileged 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines by three-component condensation between aldehyde, malononitrile, and thiol using diethylamine as a catalyst. Ambient temperature and avoidance of conventional work-up as well as purification procedure qualify this cost-effective protocol for ``green synthesis.''
Keywords: 5-dicarbonitriles; diethylamine; green chemistry; multicomponent reactions; organocatalyst; pyridine-3

Sulfamic acid-catalyzed, environmentally benign synthesis of bis-tetronic acids at ambient temperature - Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (Research on Chemical Intermediates, 2017)
An enviro-economic protocol has been described for the synthesis of bis-tetronic acids by pseudo-three-component condensation between aldehydes/isatins and tetronic acid using sulfamic acid as a solid acid catalyst. Easy commercial availability of the catalyst at extremely low cost, excellent yields and avoidance of conventional purification procedures are the main merits of this energy efficient protocol.